THE WEIGHT OF YOUTH: EXPLORING THE IMPACT OF EXCESS WEIGHT ON PERSONAL LIVES - GULOMOVA GULI ABDUSAMATOVNA (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This thesis examines the multifaceted impact of excess weight on the personal lives of young people. With the prevalence of obesity among youth on the rise globally, understanding the implications beyond physical health is paramount. Through a comprehensive review of literature and empirical research, this study delves into the social, psychological, and emotional ramifications of carrying extra weight during the formative years. By exploring the complex interplay between weight status and various aspects of personal well-being, this thesis aims to shed light on the challenges faced by young individuals grappling with obesity, while also identifying opportunities for intervention and support.